Ethnobotanical knowledge and medicinal plant use in Khenchela Province (Northeastern Algeria) - Sraoui, Hanane; Lazli, Amel; Faouzi, Guenadil; Loucif, Karim; Gherib, Imane (Ethnobotany Research and Applications, 2026)
Background: Alongside the development of modern healthcare systems, medicinal plants continue to play an important role in local therapeutic practices. Their sustained and growing use is largely associated with their therapeutic value and the relatively low risk of undesirable effects. In this context, the documentation of traditional plant-based knowledge is essential to prevent its gradual disappearance and to ensure its continuity over time. Methods: This ethnobotanical study was conducted to document the medicinal plant species used by inhabitants of the Khenchela region and to record their associated therapeutic uses. Data collection was carried out through structured interviews using 488 questionnaires. Results: The study recorded 85 medicinal plant species belonging to 39 botanical families. The most cited species was Artemisia herba-alba (RFC = 0.096). Asteraceae was the most represented family (15%), followed by Lamiaceae (14%) and Apiaceae (8%). Leaves were the most frequently used plant part (36%), while decoction was the dominant method of preparation (38%). The majority of reported uses targeted digestive disorders (21%), followed by respiratory and dermatological diseases (12% each). Conclusions: By providing detailed insight into local medicinal plant practices, this study contributes to the preservation of ethnobotanical knowledge and offers a reliable reference framework for future research in phytochemistry and pharmacology. Keywords: Ethnobotanical Surveys; Khenchela; Medicinal Plants; Methods of Preparation; Uses.